2022
DOI: 10.9782/jisne-d-21-00009
|View full text |Cite
|
Sign up to set email alerts
|

Youth and Parent Participation in Transition Planning in the U.S.A.: Findings from the National Longitudinal Transition Study 2012 (NLTS 2012)

Abstract: The purpose of this study was to use data from the United States' National Longitudinal Transition Study 2012 (NLTS 2012) to present descriptive information on youth and parent participation and youth's role in required Individualized Education Program (IEP)/transition planning meetings by disability category and age groupings (14-22 year olds, 14-15 year olds, and 16-22 year olds). The study found that youth and parent attendance in IEP/transition planning meetings was high across disability categories, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Finally, youth's role in the IEP meeting (the only variable for which it was possible to test equivalent thresholds) was found to function very differently across disability categories. Echoing these results, previous studies noted differences in IEP participation based on disability (Davenport et al, 2022;Johnson et al, 2022). As Davenport et al (2022) suggested, we intentionally did not group students with high-incidence disabilities together in order to better understand the differences by category.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Finally, youth's role in the IEP meeting (the only variable for which it was possible to test equivalent thresholds) was found to function very differently across disability categories. Echoing these results, previous studies noted differences in IEP participation based on disability (Davenport et al, 2022;Johnson et al, 2022). As Davenport et al (2022) suggested, we intentionally did not group students with high-incidence disabilities together in order to better understand the differences by category.…”
Section: Discussionmentioning
confidence: 61%
“…However, in other studies focused on transition planning, researchers did explore student differences based on disability category (Davenport et al, 2022;Johnson et al, 2022;. Both Johnson et al (2022) and used logistic regression to examine differences in transition planning by disability.…”
mentioning
confidence: 99%
See 3 more Smart Citations